Dinamika Populasi Azotobacter pada Tanah Ultisol Pertanaman Nanas: Pengaruh Kedalaman Bajak dan Jenis Kompos - Sumardi, Sumardi; Ramadhani, Winih Sekaringtyas; Handayani, Kusuma; Triyono, Sugeng; Dermiyati, Dermiyati; Yusnaini, Sri; Pamela, Ahmad Bintang (Jurnal Ilmiah Biologi UMA (JIBIOMA), 2025)
The decline in pineapple production in Lampung Tengah regency occurred in 2023, where the decline reached 16.4% of the pineapple production in 2022 (8.6 million quintals). The decline in pineapple production came from PT Great Giant Pineapple (PT GGP), with the problem of accumulation of pineapple plant litter polymers on ultisol land. The solution that emerged was the adding of biochar, vermicompost and Azotobacter (LOB), with various plowing depth. The aim of this research was to determine the dynamics of Azotobacter population (log CFU g-1) in the ultisol soil of PT GGP’s pineapple plantations which were influenced by plowing depth, compost mixture and interaction between them. The supporting variables were the temperature (0C), water content (%), pH and soil organic carbon (%). Data analysis included ANOVA (α 5%), Tukey’s HSD Test (α 5%) and Pearson R Test (α 1%). The results showed that the Azotobacter population in pre-planting (PT) samples differed significantly between plowing depth, compost mixture and the interaction of the two factors. Deep plow treatment (± 40 cm) with finely chopped pineapple litter (L1) and application of premium GGP’s compost + LOB (P3) was the best treatment, with 4,96 log CFU g-1 Azotobacter population. Azotobacter population correlated not significantly with any supporting variables.